Isolation of Bacillus sp. A5.3 Strain with Keratinolytic Activity - Saniya Aktayeva; Kairat Baltin; Assel Kiribayeva; Zhiger Akishev; Dmitriy Silayev; Yerlan Ramankulov; Bekbolat Khassenov (Biology, 2022)
Environmental safety and economic factors necessitate a search for new ways of processing poultry farm feathers, which are 90% β-keratin and can be used as a cheap source of amino acids and peptones. In this study, feather-decomposing bacteria were isolated from a site of accumulation of rotten feathers and identified as Bacillus. Among them, the Bacillus sp. A5.3 isolate showed the best keratinolytic properties. Scanning electron microscopy indicated that Bacillus sp. A5.3 cells closely adhere to the feather surface while degrading the feather. It was found that Bacillus sp. A5.3 secretes thermostable alkaline proteolytic and keratinolytic enzymes. Zymographic analysis of the enzymatic extract toward bovine serum albumin, casein, gelatin, and β-keratin revealed the presence of proteases and keratinases with molecular weights 20–250 kDa. The proteolytic and keratinolytic enzymes predominantly belong to the serine protease family. Proteome analysis of the secreted proteins by nano-HPLC coupled with Q-TOF mass spectrometry identified 154 proteins, 13 of which are proteases and peptidases. Thus, strain Bacillus sp. A5.3 holds great promise for use in feather-processing technologies and as a source of proteases and keratinases.